2018
DOI: 10.1002/2017ja025059
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Mesospheric Densities at Low Latitudes Using the Kunming Meteor Radar Together With SABER Temperatures

Abstract: Neutral mesospheric densities at a low latitude have been derived during April 2011 to December 2014 using data from the Kunming meteor radar in China (25.6°N, 103.8°E). The daily mean density at 90 km was estimated using the ambipolar diffusion coefficients from the meteor radar and temperatures from the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) instrument. The seasonal variations of the meteor radar‐derived density are consistent with the density from the Mass Spectrometer and In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 53 publications
2
42
0
Order By: Relevance
“…Therefore, a more in-depth discussion of these results is necessary. We found that the diurnal variation in meteor rates was affected by periodic solar radiation as given by Hajduk et al (1980), Lindblad (2003), and McIntosh and Hajduk (1977); the variation in meteor count rate reach their peaks once per year (Liu et al, 2017;Szasz et al, 2005;Yi et al, 2018;Younger et al, 2009; and the annual variation in meteor rates appears to have an inverse relationship with the 11-year solar cycle (Lindblad, 1967;Prikryl, 1983). This will be considered separately in this section.…”
Section: 1029/2018ja025906supporting
confidence: 60%
See 2 more Smart Citations
“…Therefore, a more in-depth discussion of these results is necessary. We found that the diurnal variation in meteor rates was affected by periodic solar radiation as given by Hajduk et al (1980), Lindblad (2003), and McIntosh and Hajduk (1977); the variation in meteor count rate reach their peaks once per year (Liu et al, 2017;Szasz et al, 2005;Yi et al, 2018;Younger et al, 2009; and the annual variation in meteor rates appears to have an inverse relationship with the 11-year solar cycle (Lindblad, 1967;Prikryl, 1983). This will be considered separately in this section.…”
Section: 1029/2018ja025906supporting
confidence: 60%
“…Temporally and spatially, the trends of these two parameters are affected by the external energy of the MLT system, its internal dynamics, and coupling of the thermosphere and ionosphere (Qian & Solomon, 2012). To date, information on the meteor backscatter signal has allowed us to determine variations in atmospheric neutral density (Clemesha & Batista, 2006;Lima et al, 2015;Stober et al, 2014;Takahashi et al, 2002;Yi et al, 2018) and atmospheric neutral temperature in the region of meteoroid ablation (Hocking et al, 1997;Holdsworth et al, 2006;Kozlovsky et al, 2016;Yi et al, 2018). However, neutral atmospheric conditions in the MLT region are generally determined via empirical models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, to estimate the relative errors in D a and the density, we conduct a similar approach using simultaneous meteor echoes observed by two co-located meteor radars with different frequencies (33 and 55 MHz) at Davis Station. The 33 and 55 MHz meteor radars at Davis Station are described in related studies (see, e.g., Reid et al, 2006;Younger et al, 2014). Figure 2a shows the height distributions of meteor detections in 1 km bins on 1 January and 1 July 2006 for the 33 and 55 MHz meteor radars at Davis Station.…”
Section: Meteor Radarmentioning
confidence: 97%
“…Geographic coordinates Frequency Data used in this study 2008) and geopotential height data (version 4) were restricted to data obtained within a 10 • × 20 • bounding box centered on each of the abovementioned meteor radar locations. Geometric heights, z, for Aura MLS observations were computed from geopotential heights, z g , via the equation (Younger et al, 2014), where R E (φ) is the radius of Earth at latitude φ, based on the WGS84 ellipsoid (Decker, 1986). The daily averaged MLS temperature and geometric height observations were interpolated into 1 km bins between 85 and 95 km to produce temperature profiles.…”
Section: Meteor Radarmentioning
confidence: 99%